The Relationship Between Elevated Serum Uric Acid and Risk of Stroke in Adult: An Updated and Dose–Response Meta-Analysis - Qiao, Tianci; Wu, Hongyun; Peng, Wei (Frontiers in Neurology, 2021)
Background: Uric acid (UA) is proposed as a potential risk factor for stroke in adult, yet the results from published studies are not generally accordant. Method: We included prospective studies that explored the relationship between serum UA (SUA) and strokes. In this study, strokes include ischemic stroke and hemorrhagic stroke, which consists of intracerebral hemorrhage and subarachnoid hemorrhage. The effect-size estimates were expressed as hazard ratio (HR) and 95% confidence interval (CI). Sensitivity and subgroup analyses were performed to assess the robustness of the pooled estimation and potential sources of heterogeneity between studies. Results: We meta-analyzed 19 prospective cohort articles, which involve 37,386 males and 31,163 females. Overall analyses results showed a significant association between a 1 mg/dl increase in high levels of SUA and the risk of total stroke (HR = 1.13; 95% CI: 1.09–1.18; P < 0.001), ischemic stroke (HR = 1.15; 95% CI: 1.10–1.21; P < 0.001), and hemorrhagic stroke (HR = 1.07; 95% CI: 1.00 to 1.15; P = 0.046). No significant difference was found between ischemic stroke and hemorrhagic stroke. In the subgroup analyses, the association of high SUA levels and the risk of total stroke was statistically significant in females (HR = 1.19; 95% CI: 1.12–1.26; P < 0.001) and males (HR = 1.11; 95% CI: 1.05–1.17; P < 0.001). Coincidentally, the association was also statistically significant for ischemic stroke, both in females (HR = 1.26; 95% CI: 1.17–1.36; P < 0.001) and in males (HR = 1.12; 95% CI: 1.06–1.19; P < 0.001). However, for hemorrhagic stroke, it was only statistically significant in females (HR = 1.19; 95% CI: 1.04–1.35; P = 0.01). Our dose–response research indicated the J-shaped trend between the ascending SUA levels and the higher risk of suffering from a stroke. Conclusions: Our findings indicate that elevated SUA is a significant risk factor for adult stroke, both for ischemic stroke and hemorrhagic stroke, and especially in females.